Penerapan Social Engagement Dalam URC (UMKM Review Contest) Sebagai Bentuk Komunikasi Pemasaran Pada UMKM Kota Padang Panjang - Qolbi Binuri Hidayattika; Dion Eriend (CV. ITTC INDONESIA, 2021)
This study aims to determine the application of Social Engagement in URC as a form of marketing communication in MSMEs in Padang Panjang City. To describe this research, it uses the Social Engagement theory by Bassuk, Grass and Berkman. In this theory, there are three components in Social Engagement, namely, social networks, social activities and social media. This study uses qualitative methods with data collection techniques using observation, interviews, and documentation. And using purposive sampling technique by determining certain criteria informants that support the research objectives. Informants who meet these criteria are the chairman and active members of the URC community as people who implement Social Engagement in their activities, and MSME activists who take part in URC activities. URC chooses Instagram and Facebook social media in carrying out its goals, because they are considered social media that are often used among people in various circles. The results of this study indicate that the application of Social Engagement that has been implemented is quite good and balanced. However, the obstacle found is that there are still many activists or MSMEs managed by people who are not competent and flexible in using social media. This is due to the age factor, not from the MSME activists themselves who refuse promotions through digital marketing. Of course, this is an inhibiting factor in URC carrying out its objectives.